The Risk of Subsequent Malignancies in Women With Uterine Papillary Serous or Clear Cell Endometrial Cancers. Issue 6 (1st July 2013) - Hinshaw, Hilary D.; Smith, Ashlee; Rungruang, Bunja; Kelley, Joseph L.; Beriwal, Sushil; Krivak, Thomas C.; Sukumvanich, Paniti; Olawaiye, Alexander B.
Abstract : Objective: Type II endometrial cancers include uterine papillary serous carcinoma (UPSC) and clear cell endometrial cancer (CC). Given their relative rarity, aggressive nature, and poor prognosis, little is known about the risk of subsequent malignancies at other sites. Our objective was to determine if women with UPSC or CC are at increased risk of subsequent malignancies. Type II endometrial cancers include uterine papillary serous carcinoma (UPSC) and clear cell endometrial cancer (CC). Given their relative rarity, aggressive nature, and poor prognosis, little is known about the risk of subsequent malignancies at other sites. Our objective was to determine if women with UPSC or CC are at increased risk of subsequent malignancies. Methods: Women diagnosed with UPSC or CC were identified from the SEER (Surveillance Epidemiology and End Results) Program from 1973 to 2005. Cases with a second gynecologic malignancy were excluded. Using SEER*Stat software, standardized incidence ratios (SIRs) of subsequent malignancies were calculated. Results: A total of 8045 and 1740 patients were diagnosed with UPSC and CC, respectively. Four hundred sixty-one (5.7%) of the UPSC cases were diagnosed with at least 1 additional nongynecologic malignancy. Significant associations were found with the following malignancies: the renal pelvis, soft-tissue sarcomas, acute myeloid leukemia, the bladder, and colon. Seventy-eight CC cases (4.5%) were diagnosed with at least 1 additional malignancy. In comparison with the baseline population risk, there was no statistically significant increased risk of any subsequent malignancy with a primary diagnosis of CC. Conclusions: This is the first large population-based analysis of second primary malignancies after type II endometrial cancers. Uterine papillary serous carcinoma is associated with increased risks of certain subsequent malignancies, and providers should be aware of these when following up patients with this diagnosis, especially those with stage I disease. In contrast, no such associations were found with CC in this cohort.